Taming the Big Green Elephant. Setting in Motion the Transformation Towards Sustainability. - Hernández, Ariel Macaspac (Springer VS, 2021)
In this publication it is shown, that sustainable low carbon development is a transformative process that constitutes the shifting from the initially chosen or taken pathway to another pathway as goals have been re-visited and revised to enable the system to adapt to changes. However, shifting entails transition costs that are accrued through the effects of lock-ins that have framed decisions and collective actions. The uncertainty about these costs can be overwhelming or even disruptive. This book aims to provide a comprehensive and integrated analytical framework that promotes the understanding of transformation towards sustainability. The analysis of this book is built upon negotiative perspectives to help define, design, and facilitate collective actions in order to execute the principles of sustainability.
Keywords: Nachhaltige Entwicklung; Gesellschaftsentwicklung; Nachhaltigkeit; Transformation; Wissenschaftstheorie; Fallbeispiel; Transformationsprozess; Steuerung; Internationaler Vergleich; Auswirkung; Kostenrechnung; Umweltökonomie